2021
DOI: 10.1002/agj2.20954
|View full text |Cite
|
Sign up to set email alerts
|

Forage conservation in sub‐Saharan Africa: Review of experiences, challenges, and opportunities

Abstract: Forage conservation is an important potential solution to seasonal variation in feed quality and quantity and herder-farmer conflicts in sub-Saharan Africa (SSA). Considerable variations exist in the type of forages conserved and the preservation methods across SSA. Hay from cultivated forages is commonly made with mechanical mowers and balers by large-scale commercial farms. In contrast, smallholder farmers, who dominate farming on the continent, make hay from natural pastures and straw from crop residues or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…This study used dried cassava leaves, while Wanapat et al ( 2018) supplemented cows with top silage. It has been reported that silage plays a critical role in reducing anti-nutritional contents and improving the feed quality of tree and shrub legumes (Balehegn et al, 2022), which could increase milk production in this study.…”
Section: Discussionmentioning
confidence: 71%
“…This study used dried cassava leaves, while Wanapat et al ( 2018) supplemented cows with top silage. It has been reported that silage plays a critical role in reducing anti-nutritional contents and improving the feed quality of tree and shrub legumes (Balehegn et al, 2022), which could increase milk production in this study.…”
Section: Discussionmentioning
confidence: 71%
“…However, the dry season is when goats graze freely, making such interventions less feasible. Additionally, there are significant challenges to forage preservation such as investment, climate, education, and social hurdles (Balehegn et al, 2022). Whilst goat selling/trading does occur year round, there is a peak through July and August (Kaumbata et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, frequent clipping/defoliation intervals are preferred in Kenya for daily feed requirements and are imperative in smallholder systems typical in agropastoral areas (Mwendia et al, 2022). This is because many farmers in the semi‐arid lands have not yet fully embraced feed conservation (Balehegn et al, 2022), thus the need for regular feed acquisition for their livestock. On the other hand, as noted earlier, fodder cultivation has gained a foothold in semi‐arid Kenya and this has seen some farmers only cutting their grasses after seed harvesting (Lugusa, 2015; Omollo, 2017).…”
Section: Discussionmentioning
confidence: 99%